Is print dying? A critical analysis of the digital convergence of West Java media from a postmodern perspective - Astuti, Dyah Rahmi; Muhaemin, Enjang Muhaemin; Maarif, Abdul Azis; Wahab, Encep Dul; Muchtar, Khoiruddin (Bricolage : Jurnal Magister Ilmu Komunikasi, 2025)
This study aims to explore how local print media in West Java maintain their business existence amidst the competition in the media industry and the development of the digital era. This study uses a case study method with data collection techniques of interviews with local media editors-in-chief, observations of print media activities, and documentation studies of documents related to print media activities in maintaining their business. The influence of the digital era on print media business patterns has forced mass media to transform in order to continue to exist. This study found several important points related to local print media in West Java, namely: having closeness to the regional and city or provincial governments of West Java so that when there is a grant from the government, they always receive it; print media has long been a government partner for advertising and publication of government activities; Advertising costs in print media are more affordable compared to national print media, plus the closeness of local print media to the people of West Java and social media facilities that local print media already have that can be utilized by the government for additional advertising and publication, and there are still loyal readers of local print media. Local print media leaders have additional tasks to develop media businesses.